Conceptual content of the legal integration: contemporary discussions and the way of constructive dia-logue - Хірсін, Андрій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The modern political integrative processes involve the correspondent integration in sphere of legal regulation. But one of the essential problems in this respect is the disagreement about the conceptual content of the legal integration, as well as about the approaches to its realization. Thus, the analysis of the ways of this problem’s solving is the main subject of proposed article. Integration that has covered almost all aspects of life in the modern world has become fundamental factor in review of established ideas about targets, functionalities and mechanisms of the legal regulation. The purpose of the article. Analysis of the contemporary discussions about the content of the concept of "legal integration" in order to determine the most constructive directions for optimization regulation in the integrated political and legal space.